REVIEWS - Prag, Kay (Journal of Semitic studies, 2003)
The Archaeology of Jordan and Beyond: Essays in Honor of James A. Sauer (Studies in the Archaeology and History of the Levant 1) Lawrence E.Stager, Joseph A.Greene, Michael D.Coogan (eds), Eisenbrauns, Winona Lake , 2000. Pp. xvi + 529 Price: $85.00 . ISBN: 1-57506-901-6.